Composite prepreg, preform using same, fiber-reinforced composite material joint, and manufacturing method thereof
The composite prepreg with alternating regions of thermosetting resins (a) and (b) addresses bonding challenges in fiber-reinforced composites, ensuring strong and flexible joint formation.
Patent Information
- Application Number
- JP2020564964
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2020-11-12
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-11-12
AI Technical Summary
Fiber-reinforced composite materials face challenges in bonding with other members due to issues like bonding failure at the interface and reduced strength at drilled holes, especially when using thermoplastic resins, and thermosetting resins are difficult to bond firmly after curing.
A composite prepreg is developed with regions containing thermosetting resins (a) and (b) having different gelation times and exotherm onset temperatures, allowing for sequential curing and improved bonding strength by alternating regions (A) and (B) on the surface, optimizing the area ratio and distribution pattern.
Enables easy and strong bonding of thermosetting fiber-reinforced composite materials with other members, allowing for multiple joints with enhanced design freedom and reduced warpage from curing shrinkage.
Smart Images

Figure 0007604894000003 
Figure 0007604894000004 
Figure 0007604894000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a prepreg that enables thermosetting fiber-reinforced composite materials to be easily joined and that is used to form a joined body having excellent joining strength. [Background technology]
[0002] Fiber-reinforced composite materials, which use thermosetting or thermoplastic resins as a matrix resin and combine them with reinforcing fibers such as carbon fiber or glass fiber, are lightweight yet have excellent mechanical properties such as strength and rigidity, as well as heat resistance and corrosion resistance, and are therefore used in many fields such as aerospace, automobiles, railway vehicles, ships, civil engineering and construction, and sporting goods.
[0003] In general, fiber-reinforced composite materials are not suitable for manufacturing parts or molded bodies having complex shapes in a single molding process. In order to form complex shapes, it is necessary to prepare a member made of the fiber-reinforced composite material and then join it to another member. When used as a structural member or semi-structural member for aircraft or automobiles, currently, joining methods using adhesives or joining methods using mechanical fastening such as rivets are used. However, when adhesives are used, there is a possibility that poor joining due to peeling may occur at the interface between the molded body of the fiber-reinforced composite material and the other member. In addition, in the case of mechanical fastening, holes are drilled in the fiber-reinforced composite material and the other member, which may reduce the strength of the holes.
[0004] Fiber-reinforced composite materials using a thermoplastic resin as the matrix resin can be joined to other members using thermoplastic resins by heat welding, and therefore the process can be relatively simplified. For example, Patent Document 1 discloses a fiber-reinforced resin laminate in which a thermosetting resin layer and a thermoplastic resin layer are joined by forming an uneven boundary surface, and this method can provide a joined body with excellent joining strength. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2004 / 060658 Summary of the Invention [Problem to be solved by the invention]
[0006] In the bonding technique using a thermoplastic resin described in Patent Document 1, the bonding surface remelts and peels off at high temperatures, which can cause heat resistance issues. For this reason, a simple bonding technique using a thermosetting resin that has excellent bonding strength with another member has been desired. In particular, when a thermosetting resin is sufficiently heated and cured, it does not remelt and has excellent heat resistance, but after curing, it becomes difficult to bond firmly with another member. For this reason, for example, when it is necessary to bond two or more members, the curing reaction may proceed sufficiently, and sufficient bonding strength may not be obtained for all the members that need to be bonded.
[0007] An object of the present invention is to provide a prepreg, in a thermosetting fiber-reinforced composite material, that enables easy bonding with excellent bonding strength to another member, particularly to two or more members. [Means for solving the problem]
[0008] The present invention, which aims to solve the above problems, is mainly characterized by a composite prepreg that includes a region (A) containing a thermosetting resin (a) and reinforcing fibers, and a region (B) containing a thermosetting resin (b) and reinforcing fibers, and satisfies conditions (i) and (ii) or satisfies conditions (ii) and (iii). (i) The thermosetting resin (b) has a longer gelation time than the thermosetting resin (a), and in at least a part of the temperature range of 40°C or higher and 180°C or lower, the gelation time Ta of the thermosetting resin (a) and the gelation time Tb of the thermosetting resin (b) satisfy Ta / Tb≦0.8. (ii) The proportion of the region (A) on the surface of the composite prepreg is 20 to 80%. (iii) the thermosetting resin (b) has a higher heat generation initiation temperature than the thermosetting resin (a), and in a differential scanning calorimetry chart measured at 5°C / min from a starting temperature of 40°C, the heat generation initiation temperature Ea of the thermosetting resin (a) and the heat generation initiation temperature Eb of the thermosetting resin (b) satisfy Eb-Ea≧30.
[0009] The present invention also includes a composite prepreg that satisfies all of the above conditions (i) to (iii). Effect of the Invention
[0010] The composite prepreg of the present invention enables a thermosetting fiber-reinforced composite material to be joined to another member simply and with excellent strength, and further enables easy joining to two or more members. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a schematic diagram showing one embodiment of a composite prepreg having regions (A) and (B) distributed in stripes in the in-plane direction on both surfaces. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of a composite prepreg having regions (A) and regions (B) distributed in a patchwork pattern in the in-plane direction on both surfaces. [Diagram 3] FIG. 2 is a schematic diagram showing one embodiment of a preform obtained by laminating another prepreg containing a thermosetting resin (a) on the composite prepreg of the present invention. [Figure 4] FIG. 3 is a schematic diagram showing one embodiment of a fiber-reinforced composite material joint in which another prepreg containing a thermosetting resin (a) and yet another prepreg containing a thermosetting resin (b) are joined via the composite prepreg having the configuration of FIG. 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described below.
[0013] <Composite prepreg> The composite prepreg of the present invention is composed of a region (A) containing a thermosetting resin (a) and reinforcing fibers, and a region (B) containing a thermosetting resin (b) and reinforcing fibers. With this configuration, the region (A) and the region (B) with different curing behaviors can be formed on the surface, so that the number of times that the prepreg can be joined to other members can be increased compared to a prepreg containing a single thermosetting resin, and the composite prepreg of the present invention is excellent in terms of design freedom in the joining process. Hereinafter, the composite prepreg of the present invention will be described with reference to the drawings as appropriate, but the present invention is not limited to these drawings. However, as will be easily understood by those skilled in the art, the description of the embodiments described in the drawings can also function as a description of the composite prepreg of the present invention as a higher concept.
[0014] FIG. 1 is a schematic diagram showing an embodiment of a composite prepreg according to the present invention, in which the region (A) 6 and the region (B) 7 are distributed in a stripe pattern in the in-plane direction on the surface. As shown in FIG. 1, the region (A) and the region (B) are alternately arranged in the in-plane direction, so that the region (A) 8 and the region (B) 9 appearing on the surface of the composite prepreg are alternately present in a stripe pattern. FIG. 2 is a schematic diagram showing an embodiment of a composite prepreg in which the region (A) 8 and the region (B) 9 on the surface are distributed in a patchwork pattern in the in-plane direction. In this embodiment, the region (A) and the region (B) cross each other to form a composite prepreg while reinforcing each other, and the region (A) 8 and the region (B) 9 on the surface of the composite prepreg obtained by such a configuration are present in a patchwork pattern in the in-plane direction. As shown in these examples, the composite prepreg of the present invention has both the region (A) and the region (B) present on its surface.
[0015] In the present invention, the first embodiment of the composite prepreg satisfies the conditions (i) and (ii). The thermosetting resin (b) in this embodiment is a thermosetting resin that has a longer gelation time, i.e., a longer time required for curing, than the thermosetting resin (a). In the composite prepreg, by using a thermosetting resin (a) and a thermosetting resin (b) that have a significant difference in gelation time, it becomes possible to combine a plurality of curing behaviors in a single prepreg, and it becomes possible to bond thermosetting fiber-reinforced composite materials easily and in a state with excellent bonding strength. Specifically, the following condition (i) is satisfied. (i) Thermosetting resin (b) has a longer gelation time than thermosetting resin (a), and in at least a part of the temperature range of 40°C or higher and 180°C or lower, the gelation time Ta of thermosetting resin (a) and the gelation time Tb of thermosetting resin (b) satisfy Ta / Tb≦0.8.
[0016] By satisfying the condition (i), in a state where the thermosetting resin (a) and the thermosetting resin (b) coexist, a composite prepreg can be obtained in which the thermosetting resin (a) is cured while the thermosetting resin (b) is in an uncured state. The Ta / Tb is preferably 0.7 or less, more preferably 0.6 or less. By setting it in this range, the time during which the thermosetting resin (b) can be in an uncured state can be extended relative to the time required for curing the thermosetting resin (a), and workability is excellent. In addition, the Ta / Tb is preferably 0.1 or more, more preferably 0.3 or more, and most preferably 0.5 or more. By setting it in this range, the time required for further curing the thermosetting resin (b) after the thermosetting resin (a) is cured can be shortened, and as a result, the joining time can be shortened.
[0017] The gelation time of the thermosetting resin in this specification is a value measured from the change in rotational torque over time using a curastometer. That is, 40°C is set as the heating start point, the heating rate is controlled at 1.7°C / min up to a predetermined temperature of 40°C or more and 180°C or less, and then while maintaining the predetermined temperature, the time required for the rotational torque to exceed 1dNm due to the progress of the curing reaction is measured, and the time required from the heating start point until the torque exceeds 1dNm can be obtained as the gelation time. For example, when measuring the gelation time at 180°C, 40°C is set as the heating start point, the heating rate is controlled at 1.7°C / min up to 180°C, and then while maintaining the temperature at 180°C, the time required for the rotational torque to exceed 1dNm due to the progress of the curing reaction is measured, and the time required from the heating start point until the torque exceeds 1dNm can be obtained as the gelation time. In the present invention, if there is such a difference in gelation time between the thermosetting resin (a) and the thermosetting resin (b) in at least a part of the temperature range of 40°C or more and 180°C or less, the temperature range can be used as the curing temperature to perform the above-mentioned sequential curing.
[0018] From the viewpoint of workability, Ta / Tb is preferably in the above range in at least a part of the temperature range of 100°C or higher and 180°C or lower, and more preferably in the above range at 180°C.
[0019] Moreover, Ta / Tb is preferably within the above range over the entire temperature range of 100° C. or more and 180° C. or less, and more preferably within the above range over the entire temperature range of 40° C. or more and 180° C. or less. By using such a combination of thermosetting resin (a) and thermosetting resin (b), it is possible to increase the degree of freedom in the production conditions when producing a fiber-reinforced composite material joint, which will be described later.
[0020] Moreover, the prepreg of the present invention satisfies the following condition (ii). (ii) The area ratio of region (A) on the surface of the composite prepreg is 20 to 80%.
[0021] The area ratio of the region (A) on the surface of the composite prepreg is the area ratio [%] obtained by dividing the sum of the areas of the region (A) on a certain surface of the prepreg by the sum of the areas of the region (A) and the region (B) on the surface, and multiplying the result by 100. The area ratio is preferably 30 to 70%, more preferably 40 to 60%, and even more preferably 45 to 55%. By setting the area ratio in this range, when the composite prepreg is used as an adhesive layer, it is possible to leave a sufficient area of the region (B) containing the thermosetting resin (b) that cures slower than the thermosetting resin (a) in an uncured state on the prepreg surface even after the bonding process via the curing of the region (A), and it is possible to further bond other adherends through the region (B).
[0022] The composite prepreg has two surfaces, a front and a back, in the out-of-plane direction (the direction perpendicular to the in-plane direction, i.e., the direction perpendicular to the prepreg surface), and in the present invention, the proportion of the area (A) on the composite prepreg surface satisfies condition (ii) on both the front and back surfaces. In this specification, the exposed flat surface extending in the out-of-plane direction at the end of the composite prepreg is called the side surface.
[0023] In the present invention, the second embodiment of the composite prepreg satisfies the above-mentioned condition (ii) and the below-mentioned condition (iii). In this embodiment, the thermosetting resin (b) is a thermosetting resin having a higher heat generation start temperature, i.e., a higher temperature required for the start of a curing reaction, than the thermosetting resin (a). In the composite prepreg, by using thermosetting resins (a) and (b) having significantly different curing temperatures, it becomes possible to combine a plurality of curing behaviors in a single prepreg, and it becomes possible to bond thermosetting fiber-reinforced composite materials easily and in a state with excellent bonding strength.
[0024] Specifically, condition (iii) is as follows: (iii) Thermosetting resin (b) has a higher heat generation initiation temperature than thermosetting resin (a), and in a differential scanning calorimetry analysis chart measured at 5°C / min with a starting temperature of 40°C, the relationship between the heat generation initiation temperature Ea of thermosetting resin (a) and the heat generation initiation temperature Eb of thermosetting resin (b) is Eb-Ea≧30.
[0025] By satisfying the condition (iii), in a state where the thermosetting resin (a) and the thermosetting resin (b) coexist, a composite prepreg can be obtained in which the thermosetting resin (a) is cured while the thermosetting resin (b) is in an uncured state. The upper limit of the Eb-Ea is preferably 200 or less, more preferably 150 or less, and even more preferably 100 or less, and the lower limit is preferably 30 or more, more preferably 45 or more, and even more preferably 50 or more. By setting it in this range, the time during which the thermosetting resin (b) can be kept in an uncured state can be extended even after the thermosetting resin (a) starts its curing reaction with an increase in temperature, and workability is excellent.
[0026] In this specification, the heat generation start temperature of a thermosetting resin is a value measured from the change in heat generation amount over time using a differential scanning calorimeter. That is, the heating start temperature is 40°C, the heating rate is controlled at 5°C / min to a predetermined temperature between 40°C and 300°C, and the heat generation amount generated by the curing reaction of the thermosetting resin during the measurement is measured and plotted on a differential scanning calorimeter chart. The heat generation start temperature is the rising point of the heat generation peak (the point where 0.2 W / g heat generation is generated from the baseline) in the differential scanning calorimeter chart.
[0027] From the viewpoint of workability, Ea is preferably from 40° C. to 200° C., and more preferably from 100° C. to less than 150° C. Eb is preferably from 100° C. to 300° C., and more preferably from 150° C. to 200° C. By controlling Ea and Eb within such ranges and combining them, the curing reaction in producing a fiber-reinforced composite material joint, which will be described later, is easily controlled, and workability is excellent.
[0028] The composite prepreg of the present invention that satisfies the above conditions (i) and (ii), or conditions (ii) and (iii), preferably has regions (A) and (B) distributed in a stripe or patchwork pattern in the in-plane direction on its surface. The stripe pattern refers to a state in which the region (A) that is continuous over the entire length of the composite prepreg and the region (B) that is also continuous over the entire length of the composite prepreg alternate on the surface of the composite prepreg, as shown in FIG. 1, for example. In the embodiment shown in FIG. 1, rectangular regions (A) and similarly rectangular regions (B) alternate on both surfaces of the composite prepreg, sharing their long sides. The regions (A) and (B) that appear on the surface are not limited to rectangular shapes, and may be square or trapezoidal. The patchwork pattern refers to a state in which the regions (A) and (B), each of which is polygonal, preferably quadrangular, exist on the surface of the prepreg, sharing two or more sides, as shown in FIG. 2. It is preferable that the regions (A) and (B) are distributed in a stripe or patchwork pattern in the in-plane direction, since this makes it easier to uniformize the bonding strength in the in-plane direction of the composite prepreg. From the viewpoint of uniformity of bonding strength, it is more preferable that both regions are distributed in a patchwork pattern on the surface of the composite prepreg.
[0029] When the regions (A) and (B) are distributed in a patchwork pattern on the surface of the composite prepreg, the regions (A) that are continuous in one direction and the regions (B) that are continuous in a direction intersecting the direction intersecting the direction may be intersected with each other, as shown in Fig. 2. In this case, the regions (A) and (B) overlap in the out-of-plane direction. The composite prepreg obtained by such a configuration is preferable because the regions (A) and (B) exposed on the surface are each continuous inside the composite prepreg, and the bonding strength can be increased by the reinforcing effect of the reinforcing fibers.
[0030] In the composite prepreg of the present invention, the region (A) and the region (B) do not have to overlap in the out-of-plane direction. By arranging the region (A) and the region (B) so that they do not overlap in the out-of-plane direction as in the embodiment of Fig. 1, the thickness in the out-of-plane direction can be made thinner than when the region (A) and the region (B) intersect as in the embodiment of Fig. 2.
[0031] In the present invention, it is preferable that the region (A) is composed of a strand-like prepreg (A') containing a thermosetting resin (a) and reinforcing fibers, and the region (B) is composed of a strand-like prepreg (B') containing a thermosetting resin (b) and reinforcing fibers. Here, the strand-like prepreg is a reinforcing fiber bundle in which a plurality of reinforcing fibers are aligned in one direction and impregnated with an uncured thermosetting resin. With such a configuration, the handling property is improved even when a complex arrangement is made in the production of the composite prepreg, and the productivity of the composite prepreg is improved.
[0032] Further, in the present invention, the composite prepreg is preferably arranged in the form of a sheet having a woven structure in which the strand-like prepreg (A') and the strand-like prepreg (B'). The woven structure here refers to a state in which the strand-like prepregs are overlapped and interlaced in the out-of-plane direction, and examples of woven structures include plain weave, twill weave, and satin weave. Among them, it is preferable to use a plain weave in which the strand-like prepreg (A') and the strand-like prepreg (B') are orthogonal to each other, as shown in the example of FIG. 2. By using such a structure, it is possible to expose the region (A) and the region (B) on the surface of the composite prepreg while forming anchoring between the region (A) and the region (B) inside the composite prepreg, and this is preferable because it is excellent in both the strength of the obtained composite prepreg itself and the bonding strength with the adherend as an adhesive layer.
[0033] In the present invention, it is also preferable that the composite prepreg is arranged in parallel with the strand-like prepreg (A') and the strand-like prepreg (B'). Arranged in parallel means that the strand-like prepregs are arranged in the in-plane direction so that their respective side surfaces are in contact with each other. A typical example is a state in which the strand-like prepreg (A') and the strand-like prepreg (B') are arranged alternately in the in-plane direction with their respective side surfaces in contact with each other as shown in the embodiment of FIG. 1. By making such a structure, a composite prepreg is obtained in which the thermosetting resin (a) and the thermosetting resin (b) are exposed while keeping the thickness of the composite prepreg thin. In this embodiment, the strand-like prepreg (A') and the strand-like prepreg (B') do not necessarily have to be arranged alternately, and there may be a portion in which any of the strand-like prepregs is arranged continuously.
[0034] The number of reinforcing fibers contained in each of the strand-like prepreg (A') and the strand-like prepreg (B') is preferably 10 or more and 800,000 or less. This range is preferable because it allows the proportion of the area (A) on the surface of the composite prepreg and its distribution state to be controlled. The number of reinforcing fibers is more preferably 100 or more and 500,000 or less, even more preferably 1,000 or more and 100,000 or less, and most preferably 2,500 or more and 25,000 or less. This range is preferable because it allows for excellent productivity when producing a composite prepreg from the strand-like prepreg and excellent bonding strength of the resulting composite prepreg.
[0035] The strand-like prepreg (A') and the strand-like prepreg (B') may contain the same or different numbers of reinforcing fibers, and this can be appropriately selected depending on the desired form and productivity of the composite prepreg.
[0036] <Thermosetting resin> Examples of thermosetting resins include unsaturated polyester resins, vinyl ester resins, epoxy resins, phenolic resins, urea resins, melamine resins, polyimide resins, cyanate ester resins, bismaleimide resins, benzoxazine resins, copolymers and modified products thereof, and resins obtained by blending at least two of these. To improve impact resistance, elastomers or rubber components may be added to the thermosetting resins.
[0037] Among them, epoxy resins are preferred from the viewpoints of excellent mechanical properties, heat resistance, and adhesion to reinforcing fibers, and ease of designing gelation time and heat generation initiation temperature. Examples of the main component of the epoxy resin include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD type epoxy resin, and bisphenol S type epoxy resin, brominated epoxy resins such as tetrabromobisphenol A diglycidyl ether, epoxy resins having a biphenyl skeleton, epoxy resins having a naphthalene skeleton, epoxy resins having a dicyclopentadiene skeleton, novolac type epoxy resins such as phenol novolac type epoxy resin and cresol novolac type epoxy resin, N,N,O-triglycidyl-m-aminophenol ... Examples of glycidylamine type epoxy resins include glycidylamine type epoxy resins such as glycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenedianiline (hereinafter sometimes referred to as "tetraglycidyldiaminodiphenylmethane"), N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, N,N-diglycidylaniline, and N,N-diglycidyl-o-toluidine, resorcinol diglycidyl ether, and triglycidyl isocyanurate. Among these, epoxy resins containing three or more glycidyl groups in one molecule are preferred because they can produce cured products with high glass transition temperatures.
[0038] Examples of the curing agent for the epoxy resin include dicyandiamide, aromatic amine compounds, phenol novolac resins, cresol novolac resins, polyphenol compounds, imidazole derivatives, tetramethylguanidine, thiourea-added amines, carboxylic acid hydrazides, carboxylic acid amides, polymercaptans, etc. Among these, the use of an aromatic amine curing agent as the curing agent is preferred because it allows the production of an epoxy resin cured product having good heat resistance. Examples of the aromatic amine compound include 3,3'-diisopropyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-4,4'-diaminodiphenyl sulfone, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3'-diisopropyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenyl sulfone, 3,3'-diisopropyl-5,5'-diethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di Examples of the aromatic amine compounds include t-butyl-5,5'-diethyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetraisopropyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-5,5'-diisopropyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetra-t-butyl-4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl ketone, 4,4'-diaminodiphenylphosphinic acid, 4,4'-diaminobenzanilide, diethyltoluenediamine, and 4,4'-diaminodiphenylmethane. These aromatic amine compounds may be used alone or in a suitable mixture of two or more.
[0039] In the first embodiment of the composite prepreg of the present invention, the thermosetting resin (a) and the thermosetting resin (b) are different resins having a significant difference in gelation time, i.e., the time required for the thermosetting resin to harden, and the thermosetting resin (b) is a thermosetting resin having a longer gelation time than the thermosetting resin (a). In order to easily achieve such a configuration, it is preferable to appropriately select the curing agent from among the main agent and the curing agent of the thermosetting resin. From the viewpoint of accelerating the gelation time, it is preferable to use 4,4'-diaminodiphenyl ketone or 4,4'-diaminodiphenyl phosphinic acid as a part or all of the curing agent of the thermosetting resin (a).
[0040] In the second embodiment of the composite prepreg of the present invention, the thermosetting resin (a) and the thermosetting resin (b) are different resins having a significant difference in heat generation start temperature, i.e., the temperature required for the curing reaction of the thermosetting resin, and the thermosetting resin (b) is a thermosetting resin having a higher heat generation start temperature than the thermosetting resin (a). In order to easily achieve such a configuration, it is preferable to appropriately select the curing agent from among the main agent and the curing agent of the thermosetting resin. From the viewpoint of lowering the heat generation start temperature and accelerating the curing, it is preferable to use 4,4'-diaminobenzanilide, diethyltoluenediamine, or 4,4'-diaminodiphenylmethane as a part or all of the curing agent of the thermosetting resin (a), and it is more preferable to use diethyltoluenediamine from the viewpoint of handling. From the viewpoint of increasing the heat generation initiation temperature and delaying curing, it is preferable to use 4,4'-diaminodiphenyl sulfone or 3,3'-diaminodiphenyl sulfone as part or all of the curing agent for the thermosetting resin (b), and it is more preferable to use 4,4'-diaminodiphenyl sulfone from the viewpoint of the high heat generation initiation temperature.
[0041] In the present invention, it is preferable that the epoxy resin composition further contains a thermoplastic resin. The thermoplastic resin is contained in order to control the tackiness of the obtained prepreg, control the fluidity of the epoxy resin when the prepreg is heat-cured, and impart toughness to the obtained fiber-reinforced composite material without impairing the heat resistance and elastic modulus. As such a thermoplastic resin, a thermoplastic resin composed of a polyaryl ether skeleton is preferable, and examples thereof include polysulfone, polyphenylsulfone, polyethersulfone, polyetherimide, polyphenylene ether, polyetheretherketone, and polyetherethersulfone. These thermoplastic resins composed of a polyaryl ether skeleton may be used alone or in combination as appropriate. Among them, polyethersulfone is preferable because it allows modification of the epoxy resin while suppressing the deterioration of the heat resistance and mechanical properties of the obtained fiber-reinforced composite material.
[0042] <Reinforced fiber> In the present invention, it is preferable that the reinforcing fiber is at least one type of reinforcing fiber selected from the group consisting of carbon fiber and glass fiber from the viewpoint of bonding strength and economic efficiency. In addition to the above, metal fiber, aromatic polyamide fiber, polyaramid fiber, alumina fiber, silicon carbide fiber, boron fiber, basalt fiber, etc. may be used as the reinforcing fiber within a range that does not impair the effects of the present invention. These may be used alone or in combination of two or more types as appropriate.
[0043] These reinforcing fibers may be surface-treated, for example by coating with a metal, by treatment with a coupling agent, by treatment with a sizing agent, or by application of an additive.
[0044] As the reinforcing fiber, carbon fiber is preferably used because of its low specific gravity, high strength, and high elastic modulus. Commercially available carbon fiber products include "TORAYCA (registered trademark)" T800G-24K, "TORAYCA (registered trademark)" T800S-24K, "TORAYCA (registered trademark)" T700G-12K, "TORAYCA (registered trademark)" T700S-12K, "TORAYCA (registered trademark)" T300-3K, and "TORAYCA (registered trademark)" T1100G-24K (all manufactured by Toray Industries, Inc.).
[0045] When using a commercially available reinforcing fiber bundle, one reinforcing fiber bundle can be divided into multiple pieces or multiple pieces can be combined to adjust the number of monofilaments, and a strand-shaped prepreg can be made through such a process. In addition, it is preferable that the monofilaments of the reinforcing fibers are oriented in one direction to form a reinforcing fiber bundle, and the monofilaments constituting such a reinforcing fiber bundle may contain partially cut fibers.
[0046] In addition, the reinforcing fibers preferably have a strand tensile strength of 3.5 GPa or more as measured in accordance with the resin-impregnated strand test method of JIS R7608 (2007), since a bonded body having excellent bond strength can be obtained. The strand tensile strength is more preferably 4.5 GPa or more.
[0047] <Method of manufacturing composite prepreg> As an example, the composite prepreg of the present invention can be produced by preparing a strand-like prepreg (A') containing a thermosetting resin (a) and reinforcing fibers as region (A) and a strand-like prepreg (B') containing a thermosetting resin (b) and reinforcing fibers as region (B), and combining and arranging the strand-like prepreg (A') and the strand-like prepreg (B'). Hereinafter, when simply described as "strand-like prepreg", it is taken to be a general term for the strand-like prepreg (A') and the strand-like prepreg (B').
[0048] Examples of the method of combining and arranging the strand-like prepreg (A') and the strand-like prepreg (B') include a method of aligning a plurality of strand-like prepregs in one direction and arranging the strand-like prepregs in the in-plane direction so that their sides are in contact with each other to form a sheet, and a method of using a plurality of strand-like prepregs as warp and weft threads to form a three-dimensional weave structure and form a sheet having a woven structure. Examples of the weave structure include plain weave, twill weave, and satin weave. In the case of a woven structure, it is preferable that one of the warp and weft threads is the strand-like prepreg (A') and the other is the strand-like prepreg (B'). This configuration is preferable because it makes it possible to obtain a composite prepreg in which the region (A) and the region (B) cross each other and reinforce each other while the region (A) and the region (B) exist in a patchwork shape in the in-plane direction on the surface. In addition, the width of the strand-like prepregs can be easily controlled by the number of reinforcing fibers contained in each of the combined strand-like prepregs, and the ratio of area (A) to area (B) on the surface of the prepregs can be easily controlled.
[0049] The strand-shaped prepreg can be manufactured by various known methods. For example, it can be manufactured by a wet method in which a thermosetting resin is dissolved in an organic solvent selected from acetone, methyl ethyl ketone, and methanol to reduce the viscosity, and then impregnated into a reinforcing fiber bundle, or a hot melt method in which a thermosetting resin is heated to reduce the viscosity without using an organic solvent, and then impregnated into a reinforcing fiber bundle. In the wet method, a reinforcing fiber bundle can be obtained by immersing the reinforcing fiber bundle in a liquid containing a thermosetting resin, then pulling it up, and evaporating the organic solvent using an oven or the like. In the hot melt method, a method in which a thermosetting resin that has been reduced in viscosity by heating is directly impregnated into a reinforcing fiber bundle, or a release paper sheet with a resin film (hereinafter sometimes referred to as a "resin film") in which a thermosetting resin is once coated on a release paper or the like is first manufactured, and then a resin film is superimposed on the reinforcing fiber bundle from both sides or one side of the reinforcing fiber bundle, and the reinforcing fiber bundle is impregnated with the thermosetting resin by heating and pressurizing it, etc. can be used. As a method for producing a strand-shaped prepreg, a hot melt method in which a thermosetting resin is impregnated into a reinforcing fiber bundle without using an organic solvent is preferred, since this method leaves substantially no residual organic solvent.
[0050] The weight of the thermosetting resin in the strand-shaped prepreg is 10 g / m 2 The weight of the thermosetting resin is preferably 50 g / m or more. 2 A thickness of 100 g / m or more is preferable because it is easy to obtain a sufficient thickness for achieving superior bonding strength, and more preferably 100 g / m 2 The upper limit of the weight per unit area is not particularly limited, but from the viewpoint of the bonding strength and ease of manufacturing the composite prepreg, it is preferably 500 g / m 2 Here, the basis weight is the unit area of 1 m 2 It refers to the mass [g] of that material contained per unit.
[0051] The weight of the reinforcing fiber in the strand-shaped prepreg is 1 to 2,000 g / m 2 It is preferable that the thickness is 30 to 1,000 g / m 2More preferably, the thickness is 50 to 200 g / m 2 By setting the thickness within this range, the composite prepreg is excellent in bonding strength and productivity, which is preferable.
[0052] The mass content of the reinforcing fibers in the strand-shaped prepreg is preferably 30 to 90 mass%, more preferably 35 to 85 mass%, and further preferably 40 to 80 mass%. By setting it in this range, it is possible to achieve both the exposed area of the thermosetting resin and the reinforcing effect of the reinforcing fibers, and it is preferable because it is possible to improve the bonding strength of the composite prepreg.
[0053] <Method of manufacturing preform and fiber-reinforced composite material joint> Another aspect of the present invention is a method for producing a fiber-reinforced composite material joint, in which a first prepreg and a second prepreg containing thermosetting resins having different gelation times and heat generation start temperatures are joined together by interposing the composite prepreg of the present invention. Here, the first and second prepregs are not particularly limited as long as they contain thermosetting resins having different gelation times and heat generation start temperatures. In addition, both the first and second prepregs are prepared separately from the composite prepreg of the present invention described above, but may be configured to be included in the composite prepreg of the present invention. From the viewpoint of the joining strength between the prepregs, the combination of the first and second prepregs is preferably a prepreg containing the thermosetting resin (a) used in the composite prepreg to be interposed and a prepreg containing the thermosetting resin (b) used in the composite prepreg.
[0054] Hereinafter, a case will be described in which a prepreg containing a thermosetting resin (a) is designated as a first prepreg, a prepreg containing a thermosetting resin (b) is designated as a second prepreg, and these are joined using the composite prepreg of the present invention to obtain a fiber-reinforced composite material joint.
[0055] In the method for producing a fiber-reinforced composite material joint of the present invention, the heating for joining the first prepreg and the composite prepreg and the heating for joining the second prepreg and the composite prepreg can be carried out stepwise or simultaneously.
[0056] When the heating is performed stepwise, first, as shown in FIG. 3, a first prepreg 200 is placed on one side of the composite prepreg 10 of the present invention to prepare a preform 100, which is then heat-cured. The heating time for heat-curing the preform is set to be equal to or longer than the gelling time of the thermosetting resin (a) and shorter than the gelling time of the thermosetting resin (b), or the heating temperature for heat-curing the preform is set to be equal to or longer than the heat generation start temperature of the thermosetting resin (a) and shorter than the heat generation start temperature of the thermosetting resin (b), thereby obtaining a fiber-reinforced composite material (joined intermediate) in which the thermosetting resin (b) derived from the composite prepreg is present on the surface in an uncured state. Then, a second prepreg is further laminated on the surface of the fiber-reinforced composite material (joined intermediate) opposite to the surface on which the first prepreg is laminated, and the laminate is heat-cured to obtain a fiber-reinforced composite material joint (not shown). The heat curing after laminating the second prepreg is preferably performed by heat molding for a time longer than the gelling time of the thermosetting resin (b) or for a temperature longer than the heat generation initiation temperature of the thermosetting resin (b).
[0057] In addition, when heating for bonding the first prepreg 200 and the composite prepreg 10 and heating for bonding the second prepreg and the composite prepreg 10 are performed simultaneously, for example, they can be performed as follows. That is, a preform is prepared by disposing a first prepreg containing a thermosetting resin (a) on one side of the composite prepreg of the present invention and disposing a second prepreg containing a thermosetting resin (b) on the other side, and then heat curing is performed. By carrying out this heat curing at a time equal to or longer than the gelation time of the thermosetting resin (b) or equal to or higher than the heat generation initiation temperature of the thermosetting resin (b), a fiber-reinforced composite material joint 400 in which a cured product 600 of the first prepreg and a cured product 300 of the second prepreg are bonded via a cured product 500 of the composite prepreg can be obtained by one-stage heating, as shown in FIG. 4.
[0058] The above-mentioned manufacturing method can provide a fiber-reinforced composite joint in which a fiber-reinforced composite material containing a cured product of thermosetting resin (a) and reinforcing fibers and a fiber-reinforced composite material containing a cured product of thermosetting resin (b) and reinforcing fibers are joined via the cured product of the composite prepreg of the present invention. Such a fiber-reinforced composite joint has excellent joint strength and is less susceptible to warping due to differences in cure shrinkage rates caused by differences in the types of thermosetting resins. EXAMPLES
[0059] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to these examples. In addition, measurements of various properties were performed in an environment of a temperature of 23°C and a relative humidity of 50%, unless otherwise noted.
[0060] <Abbreviations used in the table> [Reinforced fiber] CF-1 A continuous carbon fiber with a total of 1,000 single fibers obtained by spinning, baking, and surface oxidation treatment from a copolymer whose main component is polyacrylonitrile. The characteristics are as follows: Single fiber diameter: 7μm Density: 1.8g / cm 3 Tensile strength: 4600MPa Tensile modulus: 220GPa
[0061] [Strand prepreg] PPG-1 40 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825 (manufactured by Mitsubishi Chemical Corporation)), 60 parts by mass of tetraglycidyl diaminodiphenylmethane ("Araldite (registered trademark)" MY721 (manufactured by Huntsman Advanced Materials)), and 10 parts by mass of polyethersulfone ("Sumikaexcel (registered trademark)" PES5003P (manufactured by Sumitomo Chemical Co., Ltd.)) were added, and the mixture was heated and kneaded to dissolve the polyethersulfone. Next, while continuing the kneading, the temperature was lowered to 100°C or less, and 10 parts by mass of 4,4'-diaminodiphenylsulfone (Seikacure S (manufactured by Wakayama Seika Kogyo Co., Ltd.)) and 50 parts by mass of 4,4'-diaminodiphenylketone were added and stirred, and the obtained kneaded product was coated on a release paper using a knife coater, and a thermosetting resin film (basis weight 50 g / m) was formed. 2 This thermosetting resin film was then coated with carbon fiber CF-1 reinforcing fiber strands (weight per unit area: 193 g / m2) aligned in one direction. 2 The strand-shaped prepreg (PPG-1) was obtained by heating and pressing the carbon fibers with a heat roll.
[0062] PPG-2 40 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825 (manufactured by Mitsubishi Chemical Corporation)), 60 parts by mass of tetraglycidyl diaminodiphenylmethane ("Araldite (registered trademark)" MY721 (manufactured by Huntsman Advanced Materials)), and 10 parts by mass of polyethersulfone ("Sumikaexcel (registered trademark)" PES5003P (manufactured by Sumitomo Chemical Co., Ltd.)) were added and mixed by heating to dissolve the polyethersulfone. Next, while continuing the kneading, the temperature was lowered to 100°C or less, and 47 parts by mass of 4,4'-diaminodiphenylsulfone (Seikacure S (manufactured by Wakayama Seika Kogyo Co., Ltd.)) was added and stirred, and the resulting kneaded product was coated on release paper using a knife coater to form a thermosetting resin film (basis weight 50 g / m 2 This thermosetting resin film was then coated with carbon fiber CF-1 reinforcing fiber strands (weight per unit area: 193 g / m2) aligned in one direction. 2The strand-shaped prepreg (PPG-2) was obtained by heating and pressing the carbon fibers with a heat roll.
[0063] PPG-3 40 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825 (manufactured by Mitsubishi Chemical Corporation)), 60 parts by mass of tetraglycidyldiaminodiphenylmethane ("Araldite (registered trademark)" MY721 (manufactured by Huntsman Advanced Materials)), and 10 parts by mass of polyethersulfone ("Sumikaexcel (registered trademark)" PES5003P (manufactured by Sumitomo Chemical Co., Ltd.)) were added and heated and kneaded to dissolve the polyethersulfone. Next, while continuing the kneading, the temperature was lowered to 100°C or less, 40 parts by mass of 4,4'-diaminodiphenyl ketone was added and stirred, and the resulting kneaded product was coated on release paper using a knife coater to form a thermosetting resin film (basis weight 50 g / m 2 This thermosetting resin film was then coated with carbon fiber CF-1 reinforcing fiber strands (weight per unit area: 193 g / m2) aligned in one direction. 2 The strand-shaped prepreg (PPG-3) was obtained by heating and pressing the carbon fibers with a heat roll.
[0064] PPG-4 40 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825 (manufactured by Mitsubishi Chemical Corporation)), 60 parts by mass of tetraglycidyldiaminodiphenylmethane ("Araldite (registered trademark)" MY721 (manufactured by Huntsman Advanced Materials)), and 10 parts by mass of polyethersulfone ("Sumikaexcel (registered trademark)" PES5003P (manufactured by Sumitomo Chemical Co., Ltd.)) were added and heated and kneaded to dissolve the polyethersulfone. Next, while continuing the kneading, the temperature was lowered to 100°C or less, 40 parts by mass of 4,4'-diaminodiphenylphosphinic acid was added and stirred, and the resulting kneaded product was coated on release paper using a knife coater to form a thermosetting resin film (basis weight 50 g / m 2This thermosetting resin film was then coated with carbon fiber CF-1 reinforcing fiber strands (weight per unit area: 193 g / m2) aligned in one direction. 2 ) and heated and pressed using a heat roll to obtain a strand-shaped prepreg (PPG-4) in which the carbon fibers were impregnated with thermosetting resin.
[0065] PPG-5 100 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825 (manufactured by Mitsubishi Chemical Corporation)) and 10 parts by mass of polyethersulfone ("Sumikaexcel" (registered trademark) PES5003P (manufactured by Sumitomo Chemical Co., Ltd.)) were added and heated and kneaded to dissolve the polyethersulfone. Next, while continuing the kneading, the temperature was lowered to 100°C or less, and 35 parts by mass of 4,4'-diaminodiphenylsulfone (Seikacure S (manufactured by Wakayama Seika Kogyo Co., Ltd.)) was added and stirred, and the resulting kneaded product was coated on release paper using a knife coater to form a thermosetting resin film (basis weight 50 g / m 2 This thermosetting resin film was then coated with carbon fiber CF-1 reinforcing fiber strands (weight per unit area: 193 g / m2) aligned in one direction. 2 ) and heated and pressed using a heat roll to obtain a strand-shaped prepreg (PPG-5) in which the carbon fibers were impregnated with thermosetting resin.
[0066] PPG-6 100 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825 (manufactured by Mitsubishi Chemical Corporation)) was heated and kneaded at 40°C, and 26 parts by mass of diethyltoluenediamine ("Aradur" (registered trademark) 5200 (manufactured by Huntsman Advanced Materials)) was added and stirred, and the resulting kneaded material was coated on release paper using a knife coater to form a thermosetting resin film (basis weight 50 g / m 2 This thermosetting resin film was then coated with carbon fiber CF-1 reinforcing fiber strands (weight per unit area: 193 g / m2) aligned in one direction. 2 The strand-shaped prepreg (PPG-6) was obtained by heating and pressing the carbon fibers with a heat roll.
[0067] PPG-7 100 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825 (manufactured by Mitsubishi Chemical Corporation)) was heated and kneaded at 40°C, to which 35 parts by mass of 4,4'-diaminodiphenyl sulfone (Seikacure S, manufactured by Wakayama Seika Kogyo Co., Ltd.) was added and stirred, and the resulting kneaded product was coated on release paper using a knife coater to produce a thermosetting resin film (basis weight 50 g / m 2 This thermosetting resin film was then coated with carbon fiber CF-1 reinforcing fiber strands (weight per unit area: 193 g / m2) aligned in one direction. 2 ) and heated and pressed using a heat roll to obtain a strand-shaped prepreg (PPG-7) in which the carbon fibers were impregnated with thermosetting resin.
[0068] PPG-8 100 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825 (manufactured by Mitsubishi Chemical Corporation)) was heated and kneaded at 40°C, to which 35 parts by mass of 3,3'-diaminodiphenyl sulfone (3,3'-DAS, manufactured by Mitsui Fine Chemicals Co., Ltd.) was added and stirred, and the resulting kneaded product was coated on release paper using a knife coater to form a thermosetting resin film (basis weight 50 g / m 2 This thermosetting resin film was then coated with carbon fiber CF-1 reinforcing fiber strands (weight per unit area: 193 g / m2) aligned in one direction. 2 ) and heated and pressed using a heat roll to obtain a strand-shaped prepreg (PPG-8) in which the carbon fibers were impregnated with thermosetting resin.
[0069] PPG-9 100 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825 (manufactured by Mitsubishi Chemical Corporation)) was heated and kneaded at 40°C, to which 33 parts by mass of 4,4'-diaminobenzanilide was added and stirred, and the resulting kneaded mixture was coated on release paper using a knife coater to produce a thermosetting resin film (basis weight 50 g / m 2This thermosetting resin film was then coated with carbon fiber CF-1 reinforcing fiber strands (weight per unit area: 193 g / m2) aligned in one direction. 2 ) and heated and pressed using a heat roll to obtain a strand-shaped prepreg (PPG-9) in which the carbon fibers were impregnated with thermosetting resin.
[0070] PPG-10 100 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825 (manufactured by Mitsubishi Chemical Corporation)) was heated and kneaded at 40°C, to which 29 parts by mass of 4,4'-diaminodiphenylmethane was added and stirred, and the resulting kneaded mixture was coated on release paper using a knife coater to form a thermosetting resin film (basis weight 50 g / m 2 This thermosetting resin film was then coated with carbon fiber CF-1 reinforcing fiber strands (weight per unit area: 193 g / m2) aligned in one direction. 2 ) and heated and pressed using a heat roll to obtain a strand-shaped prepreg (PPG-10) in which the carbon fibers were impregnated with thermosetting resin.
[0071] <Evaluation method> (1) Measurement method of gelation time The thermosetting resin was taken out of the thermosetting resin film before being used in the strand-shaped prepreg, and the curing reactivity of the epoxy resin composition was evaluated from the change over time in the rotation torque measured by a curastometer. Here, a Rubber Process Analyzer RPA2000 (manufactured by ALPHA TECHNOLOGIES) was used, and the temperature was raised from 40°C to 180°C at a rate of 1.7°C / min, and the composition was heated at 180°C for 2 hours. The gelation time was the time required from the start of heating at 40°C until the torque exceeded 1dNm. In measuring the gelation time of the thermosetting resin used in the composite prepreg itself, the composite prepreg was separated into strand-shaped prepregs, and each strand-shaped prepreg was heated and pressurized at 40°C and 5MPa for 10 minutes to cause the thermosetting resin to flow between the reinforcing fibers and extracted, which was then used for evaluation by the curastometer.
[0072] (2) Measurement method for heat generation onset temperature The thermosetting resin was taken out from the thermosetting resin film before being used for the strand-shaped prepreg, and the heat generation start temperature was evaluated using a differential scanning calorimeter. Here, the heat generation start temperature was determined as the rise point of the heat generation peak (the point where 0.2 W / g heat was generated from the baseline) in the differential scanning calorimeter chart measured at 5°C / min with a starting temperature of 40°C using a DSC Q2000 (manufactured by TA Instruments). In addition, when measuring the heat generation start temperature of the thermosetting resin used in the composite prepreg itself, the composite prepreg was separated into strand-shaped prepregs, and each strand-shaped prepreg was heated and pressurized at 40°C and 5 MPa for 10 minutes to flow the thermosetting resin between the reinforcing fibers, and the extracted thermosetting resin was used for evaluation by the differential scanning calorimeter.
[0073] (3) Method for measuring the proportion of area (A) on the surface of the composite prepreg On the surface of the composite prepreg, the area [mm 2 ] was measured, and the sum of the areas of regions (A) was divided by the sum of the areas of regions (A) and (B) and then multiplied by 100 to determine the proportion [%] of region (A) on the surface of the composite prepreg.
[0074] (4) Evaluation method for bonding using gelation time difference The composite prepreg produced in each Example and Comparative Example was cut to a width of 250 mm and a length of 12.5 mm. In addition, 500 strand-like prepregs (A') used in the composite prepreg were aligned to form a square shape with a side width of 300 mm, and four sheets were prepared, which were laminated so that the orientation of the strand-like prepreg (A') was a layer structure of [0° / 90° / 90° / 0°], and then cut to a width of 250 mm and a length of 92.5 mm to obtain a laminate. Here, the length direction was set to 0°. Furthermore, the composite prepreg and the laminate made of the prepreg (A') were arranged so that both ends in the width direction and one end in the length direction were aligned to form a preform. The preform was heated at 180°C under a pressure of 0.5 MPa for the gelation time of the thermosetting resin (a) to form a fiber-reinforced composite material.
[0075] Furthermore, 500 strand-like prepregs (B') used in the composite prepreg were aligned to form a square shape with a side of 300 mm, and four sheets were prepared, which were laminated so that the orientation of the strand-like prepregs (B') was [0° / 90° / 90° / 0°], and then cut to a width of 250 mm and a length of 92.5 mm to obtain a laminate. Then, the laminate made of the prepreg (B') was laminated with the fiber-reinforced composite material so that both ends in the width direction and one end in the length direction were aligned on the opposite side to the side where the laminate made of the prepreg (A') was aligned. Next, the fiber-reinforced composite material was formed into a bonded structure by heating at 180°C for the gelation time of the thermosetting resin (b) under a pressure of 0.5 MPa, and further cut out so that the interval in the width direction was 25 mm to prepare a test piece.
[0076] The bond strength of the obtained test pieces was evaluated based on ISO4587:1995 (JIS K6850(1999)). The bond strength [MPa] was calculated by dividing the maximum load during the test by the bond area, and was evaluated on the following three-level scale, with good and fair being considered as passing. Good: The bonding strength is 10 MPa or more. Fair: The bonding strength is 3 MPa or more and less than 10 MPa. Bad: The bonding strength is less than 3 MPa.
[0077] (5) Evaluation method for bonding using heat generation initiation temperature difference The composite prepreg produced in each Example and Comparative Example was cut to a width of 250 mm and a length of 12.5 mm. In addition, 500 strand-like prepregs (A') used in the composite prepreg were aligned to form a square shape with a side width of 300 mm, and four sheets were prepared, which were laminated so that the orientation of the strand-like prepreg (A') was a layer structure of [0° / 90° / 90° / 0°], and then cut to a width of 250 mm and a length of 92.5 mm to obtain a laminate. Here, the length direction was set to 0°. Furthermore, the composite prepreg and the laminate made of the prepreg (A') were arranged so that both ends in the width direction and one end in the length direction were aligned to form a preform. The preform was heated for 10 minutes at the heat generation start temperature of the thermosetting resin (a) under a pressure of 0.5 MPa to form a fiber-reinforced composite material.
[0078] Furthermore, 4 sheets of 500 strand-like prepregs (B') used in the composite prepreg were prepared by arranging them in a square shape with a side width of 300 mm, and these were laminated so that the orientation of the strand-like prepregs (B') was a layer structure of [0° / 90° / 90° / 0°], and then cut to a width of 250 mm and a length of 92.5 mm to obtain a laminate. Then, the laminate made of the prepreg (B') was laminated with the fiber-reinforced composite material so that both ends in the width direction and one end in the length direction were aligned on the opposite side to the side where the laminate made of the prepreg (A') was aligned. Next, a pressure of 0.5 MPa was applied at the heat generation start temperature of the thermosetting resin (b) for 120 minutes to obtain a fiber-reinforced composite material with a bonded structure, and further cut out so that the interval in the width direction was 25 mm to prepare a test piece.
[0079] The bond strength of the obtained test pieces was evaluated based on ISO4587:1995 (JIS K6850(1999)). The bond strength [MPa] was calculated by dividing the maximum load during the test by the bond area, and was evaluated on the following three-level scale, with good and fair being considered as passing. Good: The bonding strength is 10 MPa or more. Fair: The bonding strength is 3 MPa or more and less than 10 MPa. Bad: The bonding strength is less than 3 MPa.
[0080] [Example 1] PPG-1 was used as the strand-like prepreg (A'), and PPG-2 was used as the strand-like prepreg (B'). As shown in FIG. 2, 500 strand-like prepregs (A') aligned in one direction and 500 strand-like prepregs (B') aligned so that the fibers are oriented in the direction perpendicular to the direction were alternately woven to form a plain weave fabric so that the distribution of the regions (A) and (B) on the surface of the composite prepreg was patchwork-like, and a square composite prepreg with a side of 300 mm was obtained. The obtained composite prepreg was evaluated by the method described in (4) above. The evaluation results are shown in Table 1.
[0081] [Example 2] PPG-1 was used as the strand-like prepreg (A'), and PPG-2 was used as the strand-like prepreg (B'). As shown in FIG. 1, 250 strand-like prepregs (A') and (B') were arranged alternately in one direction to obtain a square composite prepreg with a side length of 300 mm, in which the regions (A) and (B) were distributed in stripes on the surface of the composite prepreg. The obtained composite prepreg was evaluated by the method described in (4) above. The evaluation results are shown in Table 1.
[0082] [Example 3] A composite prepreg was obtained in the same manner as in Example 2, except that the usage ratio of the strand-like prepreg (A') was doubled and two strand-like prepregs (A') and one strand-like prepreg (B') were arranged alternately. The obtained composite prepreg was evaluated by the method described in (4) above. The evaluation results are shown in Table 1.
[0083] [Example 4] A composite prepreg was obtained in the same manner as in Example 1, except that the strand-like prepreg (A') was changed from PPG-1 to PPG-3. The obtained composite prepreg was evaluated by the method described in (4) above. The evaluation results are shown in Table 1.
[0084] [Example 5] A composite prepreg was obtained in the same manner as in Example 1, except that the strand prepreg (A') was changed from PPG-1 to PPG-4, and the strand prepreg (B') was changed from PPG-2 to PPG-5. The obtained composite prepreg was evaluated by the method described in (4) above. The evaluation results are shown in Table 1.
[0085] [Comparative Example 1] A composite prepreg was obtained in the same manner as in Example 1, except that the strand-like prepreg (B') was changed from PPG-2 to PPG-1. The obtained composite prepreg was evaluated by the method described in (4) above. The evaluation results are shown in Table 1.
[0086] [Comparative Example 2] A composite prepreg was obtained in the same manner as in Example 1, except that the strand-like prepreg (A') was changed from PPG-1 to PPG-2. The obtained composite prepreg was evaluated by the method described in (4) above. The evaluation results are shown in Table 1.
[0087] [Comparative Example 3] A composite prepreg was obtained in the same manner as in Example 2, except that the strand-like prepreg (B') was changed from PPG-2 to PPG-1. The obtained composite prepreg was evaluated by the method described in (4) above. The evaluation results are shown in Table 1.
[0088] [Comparative Example 4] A composite prepreg was obtained in the same manner as in Example 1, except that the strand-like prepreg (A') was changed from PPG-1 to PPG-5. The obtained composite prepreg was evaluated by the method described in (4) above. The evaluation results are shown in Table 1.
[0089] [Table 1]
[0090] [Example 6] PPG-6 was used as the strand-like prepreg (A'), and PPG-7 was used as the strand-like prepreg (B'). As shown in FIG. 1, 250 strand-like prepregs (A') and (B') were arranged alternately in one direction to obtain a square composite prepreg with a side length of 300 mm, in which the regions (A) and (B) were distributed in stripes on the surface of the composite prepreg. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0091] [Example 7] PPG-6 was used as the strand-like prepreg (A'), and PPG-8 was used as the strand-like prepreg (B'). As shown in FIG. 1, 250 strand-like prepregs (A') and (B') were arranged alternately in one direction to obtain a square composite prepreg with a side length of 300 mm, in which the regions (A) and (B) were distributed in stripes on the surface of the composite prepreg. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0092] [Example 8] PPG-9 was used as the strand-like prepreg (A'), and PPG-8 was used as the strand-like prepreg (B'). As shown in FIG. 1, 250 strand-like prepregs (A') and (B') were arranged alternately in one direction to obtain a square composite prepreg with a side length of 300 mm, in which the regions (A) and (B) were distributed in stripes on the surface of the composite prepreg. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0093] [Example 9] A composite prepreg was obtained in the same manner as in Example 8, except that the usage ratio of the strand-like prepreg (A') was doubled and two strand-like prepregs (A') and one strand-like prepreg (B') were arranged alternately. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 1.
[0094] [Comparative Example 5] PPG-6 was used as the strand-like prepreg (A'), and PPG-9 was used as the strand-like prepreg (B'). As shown in FIG. 1, 250 strand-like prepregs (A') and (B') were arranged alternately in one direction to obtain a square composite prepreg with a side length of 300 mm, in which the regions (A) and (B) were distributed in stripes on the surface of the composite prepreg. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0095] [Comparative Example 6] PPG-10 was used as the strand-like prepreg (A'), and PPG-6 was used as the strand-like prepreg (B'). As shown in FIG. 1, 250 strand-like prepregs (A') and (B') were arranged alternately in one direction to obtain a square composite prepreg with a side length of 300 mm, in which the regions (A) and (B) were distributed in stripes on the surface of the composite prepreg. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0096] [Comparative Example 7] PPG-7 was used as the strand-like prepreg (A'), and PPG-7 was used as the strand-like prepreg (B'). As shown in FIG. 1, 250 strand-like prepregs (A') and (B') were arranged alternately in one direction to obtain a square composite prepreg with a side length of 300 mm, in which the regions (A) and (B) were distributed in stripes on the surface of the composite prepreg. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0097] [Comparative Example 8] PPG-6 was used as the strand-like prepreg (A'), and PPG-6 was used as the strand-like prepreg (B'). As shown in FIG. 1, 250 strand-like prepregs (A') and (B') were arranged alternately in one direction to obtain a square composite prepreg with a side length of 300 mm, in which the regions (A) and (B) were distributed in stripes on the surface of the composite prepreg. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0098] [Example 10] PPG-6 was used as the strand-like prepreg (A'), and PPG-7 was used as the strand-like prepreg (B'). As shown in FIG. 2, 500 strand-like prepregs (A') aligned in one direction and 500 strand-like prepregs (B') aligned so that the fibers are oriented in the direction perpendicular to the direction were alternately woven to form a plain weave fabric so that the distribution of the regions (A) and (B) on the surface of the composite prepreg was patchwork-like, and a square composite prepreg with a side of 300 mm was obtained. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0099] [Example 11] PPG-6 was used as the strand-like prepreg (A'), and PPG-8 was used as the strand-like prepreg (B'). As shown in FIG. 2, 500 strand-like prepregs (A') aligned in one direction and 500 strand-like prepregs (B') aligned so that the fibers are oriented in the direction perpendicular to the direction were alternately woven to form a plain weave fabric so that the distribution of the regions (A) and (B) on the surface of the composite prepreg was patchwork-like, and a square composite prepreg with a side of 300 mm was obtained. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0100] [Example 12] PPG-9 was used as the strand-like prepreg (A'), and PPG-8 was used as the strand-like prepreg (B'). As shown in FIG. 2, 500 strand-like prepregs (A') aligned in one direction and 500 strand-like prepregs (B') aligned so that the fibers are oriented in the direction perpendicular to the direction were alternately woven to form a plain weave fabric so that the distribution of the regions (A) and (B) on the surface of the composite prepreg was patchwork-like, and a square composite prepreg with a side of 300 mm was obtained. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0101] [Comparative Example 9] PPG-6 was used as the strand-like prepreg (A'), and PPG-6 was used as the strand-like prepreg (B'). As shown in FIG. 2, 500 strand-like prepregs (A') aligned in one direction and 500 strand-like prepregs (B') aligned so that the fibers are oriented in the direction perpendicular to the direction were alternately woven to form a plain weave fabric so that the distribution of the regions (A) and (B) on the surface of the composite prepreg was patchwork-like, and a square composite prepreg with a side of 300 mm was obtained. The obtained composite prepreg was evaluated by the method described in (5) above. The evaluation results are shown in Table 2.
[0102] [Table 2] [Industrial Applicability]
[0103] The composite prepreg of the present invention can be suitably applied to products having complex shapes that require joining during the manufacture of structural members and semi-structural members for aircraft and automobiles, and housings for notebook computers. [Explanation of symbols]
[0104] 1: Composite prepreg in which region (A) and region (B) are distributed in a striped pattern in the in-plane direction 2: Thermosetting resin (a) 3: Reinforcement fiber contained in strand-shaped prepreg (A') 4: Thermosetting resin (b) 5: Reinforcement fiber contained in strand-shaped prepreg (B') 6: Area (A) 7: Area (B) 8: Area (A) on the prepreg surface 9: Area at the prepreg surface (B) 10: A composite prepreg in which the area (A) and the area (B) on the prepreg surface are distributed in a patchwork pattern in the in-plane direction. 11: Cured product of thermosetting resin (a) 12: Reinforcement fiber contained in the cured product of thermosetting resin (a) 13: Cured product of thermosetting resin (b) 14: Reinforcement fiber contained in the cured product of thermosetting resin (b) 100: A preform formed by disposing a first prepreg 200 on one side of a composite prepreg 10 200: First prepreg containing thermosetting resin (a) 300: Cured product of the second prepreg containing the thermosetting resin (b) 400: Fiber-reinforced composite material joint in which a first prepreg and a second prepreg are joined and cured via a composite prepreg 500: A cured composite prepreg in which the regions (A) and (B) on the prepreg surface are distributed in a patchwork pattern in the in-plane direction. 600: Cured product of the first prepreg containing the thermosetting resin (a)
Claims
1. A composite prepreg comprising a region (A) containing a thermosetting resin (a) and reinforcing fibers, and a region (B) containing a thermosetting resin (b) and reinforcing fibers, the region (A) being constituted by a strand-like prepreg (A') containing the thermosetting resin (a) and the reinforcing fibers, and the region (B) being constituted by a strand-like prepreg (B') containing the thermosetting resin (b) and the reinforcing fibers, and the composite prepreg satisfies conditions (i) and (ii) or satisfies conditions (ii) and (iii). (i) the thermosetting resin (b) has a longer gelation time than the thermosetting resin (a), and in at least a part of the temperature range of 40° C. or higher and 180° C. or lower, the gelation time Ta of the thermosetting resin (a) and the gelation time Tb of the thermosetting resin (b) satisfy Ta / Tb≦0.
8. (ii) the proportion of the region (A) on the surface of the composite prepreg is 20 to 80%. (iii) the thermosetting resin (b) has a higher heat generation initiation temperature than the thermosetting resin (a), and in a differential scanning calorimetry chart measured at 5°C / min with a starting temperature of 40°C, the heat generation initiation temperature Ea of the thermosetting resin (a) and the heat generation initiation temperature Eb of the thermosetting resin (b) satisfy Eb-Ea≧30.
2. 2. The composite prepreg according to claim 1, wherein the regions (A) and (B) are distributed in a stripe or patchwork pattern in an in-plane direction on a surface of the composite prepreg.
3. 3. The composite prepreg according to claim 1, wherein the strand-like prepreg (A') and the strand-like prepreg (B') are arranged in a sheet-like shape having a woven structure.
4. 3. The composite prepreg according to claim 1, wherein the strand-like prepreg (A') and the strand-like prepreg (B') are arranged in parallel.
5. The composite prepreg according to any one of claims 1 to 4, wherein the number of reinforcing fibers contained in one strand-like prepreg (A') and one strand-like prepreg (B') is 10 or more and 800,000 or less.
6. When the conditions (i) and (ii) are satisfied, the gelation time Ta of the thermosetting resin (a) and the gelation time Tb of the thermosetting resin (b) at 180 ° C. satisfy Ta / Tb ≦ 0.
8. The composite prepreg according to any one of claims 1 to 5.
7. A preform obtained by arranging a prepreg containing a thermosetting resin (a) other than the composite prepreg on at least one surface of the composite prepreg according to any one of claims 1 to 6.
8. A prepreg containing a thermosetting resin (a) other than the composite prepreg according to any one of claims 1 to 6 is arranged on one side of the composite prepreg, and a prepreg containing a thermosetting resin (b) other than the composite prepreg is arranged on the other side. A preform obtained by arranging a prepreg.
9. A fiber-reinforced composite material joint obtained by hot molding the preform according to claim 7 or 8.
10. A method for producing a fiber-reinforced composite material joint, comprising preparing a first prepreg and a second prepreg separate from the composite prepreg, and joining the first prepreg and the second prepreg by interposing the composite prepreg according to any one of claims 1 to 6.
11. 11. The method for producing a fiber-reinforced composite material joint body according to claim 10, wherein heating for bonding the first prepreg and the composite prepreg and heating for bonding the second prepreg and the composite prepreg are carried out in a stepwise manner.
12. 12. The method for producing a fiber-reinforced composite material joint according to claim 10, wherein the first prepreg is a prepreg containing a thermosetting resin (a).
13. The method for producing a fiber-reinforced composite material joint according to any one of claims 10 to 12, wherein the second prepreg is a prepreg containing a thermosetting resin (b).
Citation Information
Patent Citations
Prepreg sheet
JP1983119851A
Carbon fiber reinforcement, and preform and composite material prepared therefrom
JP2003082117A
Partially impregnated tow prepreg and apparatus for producing the same
JP2010031088A
Multilayer printed wiring board, method of manufacturing the same, prepreg, metal foil with resin, resin film, and metal foil-clad laminate
JP2012054464A
Epoxy resin composition, prepreg, carbon fiber reinforced composite material and method for producing the same
JP2019167429A
